Effect of Lentivirus-induced shRNA Silencing CXCR4 Gene on Proliferation and Apoptosis in Human Esophageal Carcinoma Cell Line Eca109 - Dao-feng WANG; Ning LOU; Xiao-dong LI (Cancer Biology & Medicine, 2010)
OBJECTIVE To discuss the application of the slow virus- induced short-hairpin RNA (vshRNA) to silence the expression of CXCR4 in EsCa cell lines Eca109, and observe the effect of silencing CXCR4 on the proliferation and apoptosis of Eca109 cells in vitro. METHODS The expression plasmid of vshRNA targeting CXCR4 was constructed, with a concurrent construction of negative vshRNA expression plasmid, and without targeting any known mRNA. Real-time quantitative PCR and Western blot assay were used to determine the change of CXCR4 expression in the post-transfected EsCa cell Eca109, and MTT assay was conducted to detect the change of proliferation in EsCa Eca109 cell after silencing the CXCR4. The flow cytometry was used to detect the change of the cell cycle and apoptosis in the post-silenced EsCa Eca109 cell in different groups. RESULTS The transfection rate was respectively (87.3 ± 1.2)% and (90.1 ± 1.4)% in the CXCR4- RNAi-LV (silent group) and NC-GFP-RNAi-LV (negative control group) cellular plasmids. The vshRNA interference resulted in a down-regulation of the CXCR4 gene mRNA and protein expressions in Eca109 cells. CXCL12 promoted the proliferation of EsCa cell lines Eca109. The speed of EsCa cell proliferation became slower in the silencing group than in the normal control (also the control) and the negative control groups (P < 0.05). However, there was no significant difference in comparison of the proliferation speeds between the negative control and the normal control groups (P > 0.05). In the silencing group, the proportion of the cells in phase G0/G1, phase S and phase G2/M was respectively (69.9 ± 5.0)%, (17.1 ± 2.5)% and (13.0 ± 7.4)%, and the apoptotic rate achieved (7.27 ± 0.50)%. In the normal control group, the proportion of the cells in phase G0/G1, S and G2/M was respectively (55.9 ± 4.6)%, (30.2 ± 3.9)% and (13.8 ± 1.4)%, and the apoptotic rate was (3.30 ± 0.70)%. In the negative control group, the proportion of cells in phase G0/G1, S and G2/M was respectively (52.7 ± 7.8)%, (25.3 ± 2.3)% and (21.9 ± 7.4)%, with an apoptotic rate of (4.03 ± 1.37)%. Compared with the normal control and negative control groups, there was an apparent growth of cells in the phase G0/G1 (P < 0.05), and a greatly increased number of cells in phase S (P < 0.05) in the silencing group. There was no significant difference in comparison of those between the normal control and negative control groups (P > 0.05). The apoptotic rate was obviously higher in the cells of the silencing group than in the normal control and the negative control groups (P < 0.05). There was no significant difference in comparison of the apoptotic rate between the normal control and the negative control groups (P >0.05). CONCLUSION CXCR4-vshRNA can specifically and effectively inhibit CXCR4 expression of Eca109 cells. CXCR4-vshRNA can inhibit the proliferation and enhance the apoptosis rate of Eca109 cells through intervening the expression of CXCR4, suggesting that CXCL12/CXCR4 might have an important role in the progression of Escc. This slow virus-induced shRNA can effectively silence the expression of CXCR4 gene in the EsCa cells; block up the biological effect of CXCL12/CXCR4 axle; and effectively inhibit the potency of proliferation in the EsCa cell line Eca109, thus advancing apoptosis. It suggests that the CXCL12/CXCR4 plays an important role in the progression of EsCa.